Data-Driven Insights to Improve Customer Experience in E-Commerce - Guruprasad, Aarthi (Digital Repository of Theses - SSBM Geneva, 2024)
In the fiercely competitive landscape of e-commerce, data-driven insights play a pivotal role in enhancing the customer experience and maintaining a competitive edge. By leveraging data analytics, e-commerce firms can gain valuable insights into customer preferences, behaviours, and trends. These insights enable firms to personalize the shopping experience, anticipate customer needs, and deliver targeted marketing campaigns. The study aims to ascertain the necessity of data-driven insights and their influence on customer experience in e-commerce firms, investigating factors affecting the usage of data-driven tools, identifying key drivers of customer experience improvement, and analyzing their impact on firm performance. A mixed-methods approach will be employed to gather data from 250 Indian e-commerce users through surveys, focusing on customer experience factors. Secondary data from various sources supplement industry trends. Statistical tests, including ANOVA, Regression, and Correlation, helps analyze patterns. The main findings of the study revealed significant relationships between various factors and customer experience in the e-commerce industry. Factors like convenience, competitive pricing, accessibility, user reviews, global reach, and trackable shipments demonstrate statistically significant associations with customer experience. Demographic characteristics such as gender, age, residence, and usage of e-commerce also exhibit strong associations with customer experience ratings. Challenges encountered by consumers while shopping online positively influence customer experience, while factors like price, product selection variety, and fast shipping significantly impact consumer decision-making. Additionally, there is a moderate positive correlation between customer support quality and overall customer experience, indicating the importance of effective customer service in enhancing the e-commerce experience. Ultimately, by harnessing the power of data,e-commerce firms can create more engaging, seamless, and personalized experiences for their customers, driving higher conversion rates, repeat purchases, and long-term business success.